Ondhâgga Bâsa, Levels of Speech in Madurese: Sociolinguistic Studies in Language Variations - Raditiyo Mirza Afiansyah (Linguistik, Terjemahan, Sastra (LINGTERSA), 2023)
This study analyzes the speech levels found in the Madurese language according to sociolinguistic studies. The level of speech is closely related to the variety of languages which is one of the study materials in sociolinguistic studies. The author also tries to find out the factors that influence the speech level of the Madurese language and the variations of the language in it. This study uses qualitative research methods and applies descriptive qualitative methods in collecting data. The data collection method is observing the research objects, recording the research objects, taking note of some information related to the research, and interviewing several informants who provide accurate informations related to the research materials. The findings of this study reveal that language variety occurs at the speech level of Madurese. Meanwhile, there are three levels of speech in Madura, namely Basa Enjâ'-iyâ, Basa Èngghi – ènten and Basa Èngghi – Bhunten. This kind of variation is due to its use among different social classes or statuses among people